Phosphatase and Tensin Homolog Is a Growth Repressor of Both Rhizoid and Gametophore Development in the Moss Physcomitrella patens. Issue 4 (13th October 2015) - Saavedra, Laura; Catarino, Rita; Heinz, Tobias; Heilmann, Ingo; Bezanilla, Magdalena; Malhó, Rui
Abstract : PTEN proteins regulate rhizoid and gametophore development in Physcomitrella patens. Abstract: Phosphatase and tensin homolog deleted on chromosome 10 (PTEN) is a lipid phosphatase implicated in cellular proliferation and survival. In animal cells, loss of PTEN leads to increased levels of phosphatidylinositol (3, 4, 5)-trisphosphate, stimulation of glucose and lipid metabolism, cellular growth, and morphological changes (related to adaptation and survival). Intriguingly, in plants, phosphatidylinositol (3, 4, 5)-trisphosphate has not been detected, and the enzymes that synthesize it were never reported. In this study we performed a genetic, biochemical, and functional characterization of the moss Physcomitrella patens PTEN gene family. P. patens has four PTENs, which are ubiquitously expressed during the entire moss life cycle. Using a knock-in approach, we show that all four genes are expressed in growing tissues, namely caulonemal and rhizoid cells. At the subcellular level, PpPTEN-green fluorescent protein fusions localized to the cytosol and the nucleus. Analysis of single and double knockouts revealed no significant phenotypes at different developmental stages, indicative of functional redundancy. However, compared with wild-type triple and quadruple pten knockouts, caulonemal cells grew faster, switched from the juvenile protonemal stage to adult gametophores earlier, and produced more rhizoids. Furthermore, analysis of lipid content and quantitative real-time polymerase chain reaction data performed in quadruple mutants revealed altered phosphoinositide levels [increase in phosphatidylinositol (3, 5)-bisphosphate and decrease in phosphatidylinositol 3-phosphate] and up-regulation of marker genes from the synthesis phase of the cell cycle (e.g. P. patens proliferating cell nuclear antigen, ribonucleotide reductase, and minichromosome maintenance ) and of the retinoblastoma-related protein gene P. patens retinoblastoma-related protein1 . Together, these results suggest that PpPTEN is a suppressor of cell growth and morphogenic development in plants.